Lymphoid microenvironments and innate lymphoid cells in the gut - Pearson, C; Uhlig, H; Powrie, F (2012)
Gut-associated lymphoid tissue (GALT) is a sensor region for luminal content and plays an important role in lymphoid maturation, activation and differentiation. It comprises isolated and aggregated lymphoid follicles, cryptopatches (CPs) and tertiary lymphoid tissue. Innate lymphoid cells (ILCs) play a central role within GALT. Prenatal GALT development is dependent on ILC lymphoid-inducer function. Postnatally, these cells rapidly respond to commensal and pathogenic intestinal bacteria, parasites and food components by polarized cytokine production [such as interleukin (IL)-22, IL-17 or IL-13] and further contribute to GALT formation and function. Here, we discuss how ILCs shape lymphoid intestinal microenvironments and act as amplifier cells for innate and adaptive immune responses. © 2012 .